Handbook of chemical technology and pollution control - Hocking, Martin B. (Academic Press, 1993)
Handbook of Chemical Technology and Pollution Control considers community, municipal, power generation, industrial, and transportation components of environmental impact. The book covers the major inorganic and organic commodity chemicals; aluminum, iron and steel, and copper prodution; pulp and paper; fermentation; petroleum production and refining. It also includes key topics and process details for major peterochemicals and large-scale consumer and engineering polymers. This single, convenient volume describes aspects of recycling at the industrial and post-consumer levels, and emphasizes a quantitative approach as used in the author's well-known lifecycle work with disposable and reusable cups.